2008
DOI: 10.1002/micr.20525
|View full text |Cite
|
Sign up to set email alerts
|

Arterialized venous free flap for reconstruction of burned face

Abstract: In this study, a forearm arterialized venous free flap (23 cm x 14 cm) was used in a 25-year-old male with facial burns sequels to reconstruct both cheeks, chin, lips, nose, columnella, nasal tip, and nostrils. It was arterialized by the facial artery to an afferent vein anastomosis. The venous flow was drained by four efferent vein to vein anastomoses. Although it developed small inferior marginal necrosis in the lower lip, the rest of the flap survived with good quality of the skin in both texture and color,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Different types of free flaps have been used for nasal resurfacing, each one with its own advantages and disadvantages (Antunes & Chalian, ; Benmeir et al, ; Iglesias et al, ; Prousskaia et al, ). These flaps were usually fasciocutaneous flap, thin in both the skin and the soft tissue, creating the contour around the nasal framework and providing adequate lining without obstructing the nasal airway (Antunes & Chalian, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of free flaps have been used for nasal resurfacing, each one with its own advantages and disadvantages (Antunes & Chalian, ; Benmeir et al, ; Iglesias et al, ; Prousskaia et al, ). These flaps were usually fasciocutaneous flap, thin in both the skin and the soft tissue, creating the contour around the nasal framework and providing adequate lining without obstructing the nasal airway (Antunes & Chalian, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports demonstrating its application in burned nose are available. Most of them were only case reports or utilizing free flaps for reconstruction the face, but not focusing on nose (De Lorenzi et al, 2001;Iglesias, Butr on, Ch avez-Muñoz, Ramos-S anchez, & Barajas-Olivas, 2008;Prousskaia et al, 2015;Rose, 2015;Winslow, Cook, Burke, & Wax, 2003). Prousskaia et al pre-sented not only six free flaps in burned nose reconstruction but also included other reconstruction methods in their series (Prousskaia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of successful tissue perfusion in AVFs is unclear, various clinical and experimental studies have confirmed skin flap survival using this unconventional technique4571016171819. AVFs may be harvested in a wide range of locations.…”
Section: Discussionmentioning
confidence: 99%
“…AVFs may be harvested in a wide range of locations. The harvest is technically less demanding and more superficial than conventional arterial pedicle flaps, permitting rapid harvest of very thin tissue57810. The advantages gained by this technique in transfer of skin flaps brings into question whether other tissues could be perfused via arterialization of the venous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation